Variable histopathology features of neuronal dyslamination in the cerebral neocortex adjacent to epilepsy‐associated vascular malformations suggest complex pathogenesis of focal cortical dysplasia ILAE type IIIc. (9th January 2022) - Miyata, Hajime; Kuwashige, Haruka; Hori, Tomokatsu; Kubota, Yuichi; Pieper, Tom; Coras, Roland; Blümcke, Ingmar; Yoshida, Yasuji
Abstract: Focal cortical dysplasia type IIIc (FCD‐IIIc) is histopathologically defined by the International League Against Epilepsy's classification scheme as abnormal cortical organization adjacent to epilepsy‐associated vascular malformations (VM). However, the incidence of FCD‐IIIc, its pathogenesis, or association with the epileptogenic condition remains to be clarified. We reviewed a retrospective series of surgical brain specimens from 14 epilepsy patients with leptomeningeal angiomatosis of Sturge‐Weber syndrome (LMA‐SWS; n = 6), cerebral cavernous malformations (CCM; n = 7), and an arteriovenous malformation (AVM; n = 1) to assess the histopathological spectrum of FCD‐IIIc patterns in VM. FCD‐IIIc was observed in all cases of LMA‐SWS and was designated as cortical pseudolaminar sclerosis (CPLS). CPLS showed a common pattern of horizontally organized layer abnormalities, including neuronal cell loss and astrogliosis, either manifesting predominantly in cortical layer (L) 3 extending variably to deeper areas with or without further extension to L2 and/or L4. Another pattern was more localized, targeting mainly L4 with extension to L3 and/or L5. Abnormal cortical layering characterized by a fusion of L2 and L3 or L4–L6 was also noted in two LMA‐SWS cases and the AVM case. No horizontal or vertical lamination abnormalities were observed in the specimens adjacent to the CCM, despite the presence of vascular congestion and dilated parenchymal veins in all VM. These findings suggest that FCD‐IIIc depends on the type of the VM and developmental timing. We further conclude that FCD‐IIIc represents a secondary lesion acquired during pre‐ and/or perinatal development rather than following a pathomechanism independent of LMA‐SWS. Further studies will be necessary to address the selective vulnerability of the developing cerebral neocortex in LMA‐SWS, including genetic, encephaloclastic, hemodynamic, or metabolic events. Abstract : Cortical neuronal dyslamination (FCD‐IIIc) adjacent to leptomeningeal angiomatosis of Sturge‐Weber syndrome (LMA‐SWS) was mainly attributed to cortical pseudolaminar sclerosis (CPLS) characterized histologically by neuronal cell loss and astrogliosis of varying thickness and depth, organized parallel to the pial surface. Abnormal cortical layering showing a fusion of L2 and L3 or L4–L6 was also noted in LMA‐SWS cases and the AVM case; however, cortical dyslamination was not identified in CCM cases. These findings suggest that FCD‐IIIc depends on the type of the vascular malformation and developmental timing and that FCD‐IIIc represents a secondary lesion during pre‐ and/or perinatal development rather than following a pathomechanism independent of LMA‐SWS.